Analysis of the Form and Function of Conjunctions in the Novel “Sang Pemimpi” by Andrea Hirata - Malau, Jemima Flora Indah; Simaremare, Juni Agus; Simorangkir, Nomi Agustina; Sihotang, Elena Damayanti (Dinamika Bahasa dan Budaya, 2024)
This research is motivated by the use of conjunctions because this use is very important, because through the use of the right conjunction, the writing delivered will be easily understood by the reader. This research also aims to describe the form of conjunctions in the novel Sang Pemimpi by Andrea Hirata. The method used is qualitative research, the data collection technique in this research is reading technique and note-taking technique. In the results of the study we will find the form and function of conjunctions from the novel Sang Pemimpi by Andrea Hirata which can be used as learning because conjunctions have an important role in order to improve in stringing words to become a cohesive sentence so that it can be understood by the reader and teaching about conjunctions is needed to increase linguistic knowledge. Keywords: form and function, conjunction